1994
DOI: 10.1200/jco.1994.12.6.1238
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of docetaxel for recurrent or metastatic non-small-cell lung cancer.

Abstract: Docetaxel administered at 100 mg/m2 intravenously every 3 weeks has significant activity against non-small-cell lung cancer, with a 33% major response rate. Primary toxicities were neutropenia, hypersensitivity, and fluid retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
60
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(63 citation statements)
references
References 18 publications
2
60
0
1
Order By: Relevance
“…Neuropathy has also been reported as a dose-dependent side-effect of treatment with paclitaxel (Taxol) (Lipton et al, 1989;Gerven et al, 1994). As expected, trials on combination chemotherapy of cisplatin and paclitaxel found a high incidence of peripheral neuropathy (Rowinsky et al, 1991;Rowinsky et al, 1993;Chaudhry et al, 1994).Peripheral neurotoxicity has been reported as a frequent, but usually mild side-effect of docetaxel in several phase I and phase II studies (Bissett et al, 1993;Extra et al, 1993;Aamdal et al, 1994;Fossella et al, 1994;Francis et al, 1994a;Francis et al, 1994b;Smyth et al, 1994;Chevallier et al, 1995; Hilkens et al, 1996;New et al, 1996). The neurotoxic effects of docetaxel in combination Chemotherapy was administered in 3-weekly regimens.…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…Neuropathy has also been reported as a dose-dependent side-effect of treatment with paclitaxel (Taxol) (Lipton et al, 1989;Gerven et al, 1994). As expected, trials on combination chemotherapy of cisplatin and paclitaxel found a high incidence of peripheral neuropathy (Rowinsky et al, 1991;Rowinsky et al, 1993;Chaudhry et al, 1994).Peripheral neurotoxicity has been reported as a frequent, but usually mild side-effect of docetaxel in several phase I and phase II studies (Bissett et al, 1993;Extra et al, 1993;Aamdal et al, 1994;Fossella et al, 1994;Francis et al, 1994a;Francis et al, 1994b;Smyth et al, 1994;Chevallier et al, 1995; Hilkens et al, 1996;New et al, 1996). The neurotoxic effects of docetaxel in combination Chemotherapy was administered in 3-weekly regimens.…”
mentioning
confidence: 76%
“…Significant correlations were present between both the cumulative dose of docetaxel and cisplatin and the post-treatment sum-score of neuropathy (P < 0.01) as well as the post-treatment VPT (P < 0.01). The neurotoxic effects of this combination were more severe than either cisplatin or docetaxel as single agent at similar doses.Keywords: neuropathy; docetaxel; cisplatin; neurotoxicity; peripheral nerves; chemotherapy Docetaxel (Taxotere) is a new semisynthetic taxoid that has demonstrated substantial clinical activity against a wide variety of solid tumours (Pazdur et al, 1993;Aamdal et al, 1994;Fossella et al, 1994;Francis et al, 1994a;Francis et al, 1994b;Smyth et al, 1994;Chevallier et al, 1995). Docetaxel inhibits tubulin depolymerization and promotes microtubule assembly, resulting in dysfunctional microtubules (Pazdur et al, 1993).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In order to avoid systemic toxicity associated with intravenous administration of docetaxel [11,22] and achieve very high local concentration of the drug [26], we incorporated docetaxel into biodegradable polymer matrices that could be implanted intratumorally into the cranial cavity. As the polymer matrix degrades, it releases the loaded drug interstitially directly to the tumor bed, bypassing limitations imposed by the blood-brain barrier and minimizing systemic exposure to the drug.…”
Section: Introductionmentioning
confidence: 99%